ANALISIS PUSAT-PUSAT PERTUMBUHAN DI KABUPATEN NAGEKEO - Gheli, Maria Fransiska; Nalle, Agus Arnold; Kiak, Novi Theresia (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 8 (2024): Vol.13.No.8. AGUSTUS 2024 [545-633], 2024)
The purpose of this study is to analyze the growth centers of Nagekeo Regency. This study uses scale histogram analysis and gravity analysis to identify growth centers in Nagekeo Regency based on service facility availability and priority in stakeholder decisions. Analyze the interaction (degree of association) between the growth center and surrounding subzones using gravity analysis. The analysis results show the center of growth or hierarchy I. (one) out of 7 (seven) sub-districts there are two sub-districts Aesesa District and Aesesa Boawae District. The districts with the highest engagement rates among the two growth hub districts are Aesesa South District and Mauponggo District. Aesesa District and South Aesesa District have an interaction strength of 1,206,408.27. While Boawae District and Mauponggo District have an interaction intensity of 1,434,281.18. Keywords: Center for Economic Growth, Scalogram, Gravity.